2010
DOI: 10.1002/jcu.20741
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac echogenic focus and fetal outcome

Abstract: The prevalence of ICEF was 6.3%. Of 31 fetuses with an isolated ICEF, outcomes of 28 fetuses are known and all neonates were reported to be normal at birth. Thus we infer that the presence of an isolated ICEF has no adverse effect on outcome of the neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In our samples, the majority of EIF were unilateral; among the cardiac chambers affected, the left ventricle was the most frequent (69.4%), which was similar to that reported by other authors 2,30 . Some studies have shown that no chromosomal karyotype abnormalities were found in fetuses with multiple EIFs 31,32 .…”
Section: Discussionsupporting
confidence: 91%
“…In our samples, the majority of EIF were unilateral; among the cardiac chambers affected, the left ventricle was the most frequent (69.4%), which was similar to that reported by other authors 2,30 . Some studies have shown that no chromosomal karyotype abnormalities were found in fetuses with multiple EIFs 31,32 .…”
Section: Discussionsupporting
confidence: 91%
“…However, these observations were not confirmed by subsequent studies . More recent investigations indicate that an isolated EIF does not confer an increased risk of aneuploidy or other adverse pregnancy outcome and should be considered a normal variant …”
Section: Discussionmentioning
confidence: 85%
“…13,14 More recent investigations indicate that an isolated EIF does not confer an increased risk of aneuploidy or other adverse pregnancy outcome and should be considered a normal variant. [15][16][17] EIFs can be found in one or both ventricles, and they may be single or multiple. 4 The most frequent finding is a single focus in the LV.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have suggested that diffuse echogenicity in the fetal heart, especially when the right ventricle is also involved, may signal a poor prognosis and deserves a further search for associated pathologies [27,28]. Postnatal cardiac functions after the presence of prenatally diagnosed IEF are not associated with myocardial dysfunction during childhood [41,43].…”
Section: Intracardiac Echogenic Focusmentioning
confidence: 99%